Enterprise integration and information architecture : a systems perspective on industrial information integration - Xu, Li D. (Advances in systems science and engineering., 2015)
This book explains how to improve industrial information integration through the application of a systems approach. It covers enterprise architecture, information architecture for enterprises, business process/work flow modeling, and enterprise information integration. Thee book provides various perspectives of modern enterprise solutions. It introduces the critical concepts of ERP, industry-oriented enterprise resource planning, and entire resource planning. It also provides guidance on how to transition from extended enterprise integration in a supply chain environment to systems-based enterprise architecture, enterprise modeling, and enterprise modeling in a supply chain environment. The book proposes a new information architecture for enterprise and supply chain management and presents modeling and integration information flows for enterprise information integration, together with the Internet of Things (IoT). It also explores the theory and methods of industrial information integration including integration approaches and enterprise application integration. --